The cat in the hat - Geisel, Theodor Seuss (Collins London, 2003)
To accompany the release of the live action movie of The Cat in the Hat, starring Mike Myers, HarperCollins are proud to present Dr. Seuss$1 (Bs original, classic tale of the coolest, hippest cat in history!s